“Triple support pocket” for placing brachytherapy plaques for anterior segment tumors - Neiwete Lomi; Deepsekhar Das; Bhavna Chawla; J Niranjana; Dhanabalan Rajasekaran; Radhika Tandon (Indian Journal of Ophthalmology, 2025)
Background: Anterior segment tumors are rare tumors with limited management options. In small-sized lesions, plaque brachytherapy is advisable. The placement techniques of plaques for anterior segment tumors are completely different from the techniques for posterior segment tumors.[1-4] In cases where the lesion is located in the medial, lateral, or inferior iris, the possibility of tilt or displacement of the plaque is higher. The gravitational pull, coupled with ocular movements, squeezes the plaque against the ocular surface and the eyelid. This leads to displacement of the plaque along with damage to the corneal epithelium. Although certain novel plaque designs have been described in the literature to prevent such complications.[5] Their regular availability in all brachytherapy units is limited. Purpose: The authors here demonstrate a novel technique of “Triple support pocket” in a case of inferior irido-ciliary melanoma. Synopsis: The video demonstrates the steps of the “triple support pocket” orientation of brachytherapy plaque placement, along with a surgical demonstration in a case of inferior irido-ciliary melanoma. The steps include first sectoral peritomy with conjunctival dissection and flap creation, followed by step 2, which involves placement of a figure of 8 pattern 5–0 ethibond suture. The points of suture entry and exit are determined by the size of the plaque. The entries and exits are 0.5–1 mm away from the plaque edge. The third step involves moving the conjunctival flap over the brachytherapy plaque. The fourth step is where a tarsorrhaphy is performed. A 42-year-old female patient presented with an inferior iris lesion, which was diagnosed as an irido-ciliary melanoma using the popular “ABCDEF” rule designed by Shield et al.[6] The tumor had a largest basal diameter of 7.32 mm and an apical thickness of 3.87 mm extending inferiorly from 6’o clock to 7’o clock. A radio-active Ruthenium 106 plaque of size 12 mm was used in the management. Centration was achieved by using ultrasound on the table. Care was taken to ensure that all the edges of the tumor is covered, and the center of the plaque corresponds to the maximum apical thickness. The authors have performed this procedure twice, and there has been no incidence of tilt of plaque or displacement. The mean duration of the two cases was 119.5 hours. Mean dose at the sclera and apex is 313 Gy and 80 Gy, respectively. At 3 months follow-up, there were no cornea-related side effects or glaucoma. Highlights: Triple support pocket orientation of plaque brachytherapy helps in the prevention of displacement or tilt of the brachytherapy plaque. Video Link: https://youtu.be/6G2wIiCbteE